The use of digital platforms and profitability perception in companies of the restaurant sector in Jalisco, Mexico (2019-2022) - Navarro Benavides, Alfonso; Arechavala Vargas, Ricardo (Acta Universitaria, 2025)
This research identifies variables influencing profitability in restaurants using digital platforms (e.g., Uber Eats, Didi, Rappi, and others) in the state of Jalisco, Mexico. The source of the data is the Restaurant Survey on the Use of Digital Platforms (2019-2022) prepared by the Institute of Statistical and Geographic Information, which examines the covid-19 crisis. It was modeled through the functions Logit and Probit, in which the dependent variable represents the perception of increased profitability. This approach made it possible to identify the main variables that directly influence this outcome. The main findings suggest that it is more likely to increase profitability in restaurants that use digital platforms when a significant proportion of their revenue comes from sales through these platforms and from rising prices.